Hyena: From the Perspective of Animal Physiology and its Impact on Jurists’ Disagreement - Taher Mohammed Abdo Sulaiman Al-Ahdal; Omar Abdullah Kolaib; Wan Mohd Yusof Wan Chik; Ahmad Iqbal Mohd Fadzli (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 3 Page (196-214)